2021
DOI: 10.3389/fgene.2021.714575
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Mapping of Late Blight Tolerance Trait in Potato (Solanum tuberosum L.)

Abstract: Uncovering the genetic basis and optimizing the late blight tolerance trait in potatoes (Solanum tuberosum L.) are crucial for potato breeding. Late blight disease is one of the most significant diseases hindering potato production. The traits of late blight tolerance were evaluated for 284 potato cultivars to identify loci significantly associated with the late blight tolerance trait. Of all, 37 and 15 were the most tolerant to disease, and 107 and 30 were the most susceptible. A total of 22,489 high-quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 42 publications
1
11
1
Order By: Relevance
“…Among them, mutation and recombination are the most important, along with biological reproduction patterns, genetic drift and selection effects. In this study, the linkage distance of 60 Kb for the tetraploid potatoes is significantly greater than that of 1 Kb in previous studies ( Wang et al., 2021 ). The possible reason for this discrepancy is that we compared all sequencing data to the 48 chromosomes of the reference tetraploid potato, which led to a significant increase in LD.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…Among them, mutation and recombination are the most important, along with biological reproduction patterns, genetic drift and selection effects. In this study, the linkage distance of 60 Kb for the tetraploid potatoes is significantly greater than that of 1 Kb in previous studies ( Wang et al., 2021 ). The possible reason for this discrepancy is that we compared all sequencing data to the 48 chromosomes of the reference tetraploid potato, which led to a significant increase in LD.…”
Section: Discussioncontrasting
confidence: 77%
“…At present, the reported studies of potato GWAS are mainly based on haploid reference genome, and few studies of GWAS use tetraploid potato reference genome. Wang et al conducted a pilot GWAS of late blight potatoes and mined 14 candidate genes (Wang et al, 2021). However, the study was limited to the reference genome version, which was selected from diploid DM potato varieties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our tip-calibrated coalescent analyses revealed that the time to the most common recent ancestor of that Clade was 32,226 BCE and not 332,580 to 142,980 BCE (Fig. 5B), as previously reported (12,44). Because the same holds true for Clade I, both clades could have coexisted in sympatry 25,000 years later when donkeys were first domesticated (Fig.…”
Section: Donkey Management Involved Inbreeding and Introgression From...supporting
confidence: 81%
“…However, the rate of degradation of C. edulis LD was very slow. This method has been successfully applied to other crops, such as M. esculenta Crantz ( Zhang et al, 2018 ) and Solanum tuberosum L. ( Wang et al, 2021 ). A detailed understanding of the demographic structure of a group of members is essential to exclude unnecessary members from the group.…”
Section: Discussionmentioning
confidence: 99%